Teknologi Fintech sebagai Agen Transformasi dalam Meningkatkan Kepercayaan Wali Santri Terhadap Layanan Keuangan Syariah di PM UQI Bogor: Fintech Technology as a Transformation Agent in Increasing the Trust of Santri Guardians in Sharia Financial Services at PM UQI Bogor - Budiarti, Sari; Morita, Ersa (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
This research aims to examine the influence of how Fintech Technology has an important role as a transformation agent in Sharia financial institutions. The research position of existing research is to establish 4 (four) hypotheses including (H1): Fintech technology has a direct positive and significant effect on transformation agents at PM UQI Bogor. (H2): Does fintech technology have a direct positive and significant effect on Sharia financial services at PM UQI Bogor. (H3): Do transformation agents have a direct positive and significant effect on sharia financial services at PM UQI Bogor. (H4): Does the Trust of Santri Guardians have a direct positive and significant effect on Sharia financial services at PM UQI Bogor. The data in this research was obtained through a questionnaire distributed via Google Form which was filled in by respondents, namely PM IUQI Santri Guardians with a total of 200 respondents. This research uses non-probability sampling, using convenience sampling. The data testing method in this research is by using Amos version 24, namely by testing the validity test, reliability test, direct hypothesis test, and full SEM model suitability test. The findings from the results of this research are that all the hypotheses proposed in this research are accepted or all are influential and significant. The findings show that the adoption of Fintech Technology has made a major contribution in improving Sharia financial services at PM UQI Bogor. Fintech technology is not just a technological tool, but is also a major catalyst in changing the way Sharia financial services are provided and accessed by Islamic boarding school parents (Khan, F., Ahmad, R., & Ali, 2020). The implications of this research are encouragement of technology adoption, the importance of transformation agents, focus on user trust. The limitations of this research are the limited sample size, limited variables and this research was conducted cross-sectionally. Suggestions for further research are expanding the scope of research to other Sharia financial institutions, developing other variables to be researched, further research can be carried out longitudinally.